Tooth extraction and immediate implant placed in infected socket with 3 years follow-up. Case report - Casco Silva , Diego Fernando (2025)
The immediate placement of dental implants post-extraction is a controversial technique due to the potential risk of failure, which is further exacerbated when performed in infected sockets. This study describes a case involving immediate implant placement following the extraction of a maxillary lateral incisor due to vertical fracture and an infected socket, along with subsequent prosthetic rehabilitation, demonstrating successful outcomes over a 3-year follow-up period. It was concluded that, in this case, osseointegration of the immediate implant in the infected socket was achieved, with favorable aesthetic and functional results up to the 3-year follow-up. Further monitoring is required to determine whether the initial socket pathology has been removed or may affect the implant's long-term performance.